2007
DOI: 10.1021/ja066834k
|View full text |Cite
|
Sign up to set email alerts
|

Defect-Site Promoted Surface Reorganization in Nanocrystalline Ceria for the Low-Temperature Activation of Ethylbenzene

Abstract: The study of the defective surface sites of many oxides has received considerable interest, as these sites are coordinately unsaturated and exhibit extraordinary activity in many catalytic reactions. 1 Most of the research work in this particular area is mainly focused on theoretical simulations. 2 However, the influence of the defect sites on the chemical nature of the oxide surface and their role in the mechanism of activation of a substrate have not yet been fully explored. In this Communication, we take th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(104 citation statements)
references
References 16 publications
3
95
0
2
Order By: Relevance
“…Recent investigations revealed a high concentration and a high stability of reactive surface Ce 3+ ions over a wide range of temperature and of oxygen partial pressure on ceria surfaces [58], and Ce 3+ and oxygen vacancies are generally believed to be the active sites on ceria surfaces and therefore refer to the Sad adsorption sites [59][60][61]. It is generally assumed that one of the different reaction steps will be rate determining, with the charge transfer step leading to dissociation being the most likely rate determining step [56,62].…”
Section: Oxygen Exchange From Co2 Atmospheresmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent investigations revealed a high concentration and a high stability of reactive surface Ce 3+ ions over a wide range of temperature and of oxygen partial pressure on ceria surfaces [58], and Ce 3+ and oxygen vacancies are generally believed to be the active sites on ceria surfaces and therefore refer to the Sad adsorption sites [59][60][61]. It is generally assumed that one of the different reaction steps will be rate determining, with the charge transfer step leading to dissociation being the most likely rate determining step [56,62].…”
Section: Oxygen Exchange From Co2 Atmospheresmentioning
confidence: 99%
“…The following reaction scheme would be conceivable in accordance with the current ideas on surface exchange from pure oxygen atmosphere [56,57] CO 2 (g) + S ad ⇒ CO 2 (ad) (10) where S ad represents a CO 2 adsorption site. Recent investigations revealed a high concentration and a high stability of reactive surface Ce 3+ ions over a wide range of temperature and of oxygen partial pressure on ceria surfaces [58], and Ce 3+ and oxygen vacancies are generally believed to be the active sites on ceria surfaces and therefore refer to the S ad adsorption sites [59][60][61].…”
Section: Oxygen Exchange From Co 2 Atmospheresmentioning
confidence: 99%
“…20 Ceria is the most industrially significant rare earth oxide catalyst mainly due to its use in three-way catalytic converters (TWC) and fluid catalytic cracking (FCC). 19,21 Recently, ceria-based materials have been investigated for use in soot removal from diesel engine exhausts, 22 volatile organic compound (VOC) degradation, 23 fuel cell technology, 24 water-gas shift reaction, 25,26 preferential CO oxidation (PROX), 27 oxidative dehydrogenation, 28 and selective hydrocarbon oxidations. 29,30 The success of ceria and ceria-based materials in catalysis is oftentimes due to facile Ce 4+ /Ce 3+ redox cycling without disruption of the fluorite lattice structure.…”
Section: 2mentioning
confidence: 99%
“…16 Zr 0.84 O 1.92 (YSZ) (100) single crystal (MTI Corp.) and patterned via metal-liftoff photolithography. The metal pattern consists of line patterns 20 µm in width and spaced 140 µm apart.…”
Section: Sample Preparationmentioning
confidence: 99%
“…15 Understanding the behavior of surface reactive species is crucial towards establishing the reaction mechanism. Ce 3+ and oxygen vacancies are thought to be the active sites on ceria surfaces [16][17][18] in reactions such as hydrolysis: ( 2 Several studies have shown that the surface concentrations of these active species can be higher than the bulk, potentially explaining ceria's high chemical activity [16][17][18][19] However, the behavior of these active surface species is not well-understood, in part because studies involving mixed-valent materials are complicated by the fact that both the bulk and the surface participate in the catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%